Reflections of Folk Pedagogics in Lithuanian Proverbs, Proverbial Phrases and Situational Sayings - Kašėtienė, Rasa (Tautosakos darbai, 2016)
The article discusses traditional upbringing of children in the Lithuanian countryside that extensively employed popular proverbs, proverbial phrases and situational sayings. The author also presents numerous examples of the folklore genre in question, illustrating this function and reflecting the folk pedagogics.The chief task of parents has always been raising honest and hard-working children; therefore, the little ones had to learn adhering to the norms of Christian morality: i.e. respecting their parents, abstaining from stealing or lying, getting used to work from early age. In addition, children were supposed to be well behaved, polite, and respectful to their elders, particularly to their grandparents, and refrain from interrupting the grown-ups. Much attention was paid to esthetic education of children. The child’s language, walking, movements, manners received esthetic appreciation; clothes and cleanliness were important as well. These characteristics grew particularly significant, when the young ones started participating in the life of the village community: having received their basic education at home, children subsequently knew the proper ways of behaving in public. The village community scrutinized the behavior of children and young people very closely; every case of misdemeanor or inappropriate acts received immediate reaction. For the sake of laconicism, people often used proverbs and proverbial phrases or situational sayings to describe typical situations; coarse or vulgar lexis was also popular. Usually, rather than scolding the misbehaved children or young people, the grown-ups were likely to gibe or sneer at them, particularly in public. Some of the sayings presented in the article applied not only to children.
Keywords: -